Intimate Dialogue with “The Bee Inside the Head” - BLAGA, Raluca (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
This paper is structured as an analytical dialogue, challenged by the performance The Bee Inside the Head by Roland Schimmelpfennig, directed by Theodor-Cristian Popescu (produced by the National Theatre of Târgu-Mures, the Liviu Rebreanu Company). Starting from the definitions proposed by Hans-Thies Lehmann in his book, Postdramatic Theatre, this analysis frames the above-mentioned theatrical performance into the realm of scenic poetry, following all the stage mechanisms that avoid the classical construction of a theatrical event.